Cloud-Based Content Synchronization Method for Collaborative Learning Environment - Lim, Geunsik; Lee, Donghwa; Suh, Sang-bum (International Journal of Advanced Corporate Learning (iJAC), 2015)
Existing online education has moved from desktop environments to mobile environments due to the proliferation of smart devices. Online educational systems running on smart devices have the advantage of allowing users to learn online regardless of the location of the users. In particular, data synchronization enables users to cooperate on contents in real time anywhere by sharing their files via cloud storage. However, users cannot collaborate by simultaneously modifying files that are shared with one another. In this paper, we propose a content collaboration method and a history management technique that are based on distributed system structure and can synchronize data shared in the cloud for multiple users and multiple devices. Our proposed system helps users performing work on the collaborative content by automatically merging updated contents of cloud files among users.